2016
DOI: 10.1002/bjs.10123
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil to lymphocyte ratio as an indicator of the malignant behaviour of hepatocellular carcinoma

Abstract: Preoperative NLR was an important prognostic factor for TNM stage I HCC after liver resection with curative intent. These results suggest that the NLR may reflect the malignant potential of HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
50
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 23 publications
8
50
0
Order By: Relevance
“…The high rate of recurrence remains a challenge for hepatic surgeons. Risk factors related with tumour characteristics are significantly related to early HCC recurrence, but the impact of viral status on recurrence is unclear, and some studies did not identify any role for hepatitis B viral status on prognosis, whilst other studies suggested that the presence of HBeAg was significantly correlated with prognosis . Propensity score matching analysis has been widely used in patients with HCC .…”
Section: Introductionmentioning
confidence: 99%
“…The high rate of recurrence remains a challenge for hepatic surgeons. Risk factors related with tumour characteristics are significantly related to early HCC recurrence, but the impact of viral status on recurrence is unclear, and some studies did not identify any role for hepatitis B viral status on prognosis, whilst other studies suggested that the presence of HBeAg was significantly correlated with prognosis . Propensity score matching analysis has been widely used in patients with HCC .…”
Section: Introductionmentioning
confidence: 99%
“…In their study, Terashima et al set the cut-off level of the NLR as the median value [19]. Another study determined the cut-off value by comparing the survival rates between NLR groups stratified according to several candidate values from 2.6 to 3.2 [28]. Several studies determined cut-off values by using receiver-operating characteristic (ROC) curves [17, 22].…”
Section: Discussionmentioning
confidence: 99%
“…According to Okamura et al, lower AFP and smaller tumor size were associated with a low NLR [28]. Although the association between the NLR and other prognostic factors could be a valid explanation for the difference in prognosis, it was still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Factors, including inflammation-based indices including neutrophil-to-lymphocyte ratio (NLR) (5), platelet-to-lymphocyte ratio (PLR) (6), prognostic nutritional index (PNI) (7) and body mass index (BMI) (8) and tumor biomarkers including topoisomerase (Topo) II-α (9) and Ki67 (10) represent independent predictors of poor OS rates in patients with HCC and enabled the refinement of current prognostic models. These novel factors may be used to determine the OS and development of preventative measures in those with high risk.…”
Section: Introductionmentioning
confidence: 99%